Epithelioid angiosarcoma: A rare cause of pericarditis and pleural effusion. (2018) - Durani, Urshila; Gallo de Moraes, Alice; Beachey, Joel; Nelson, Darlene; Robinson, Steven; Anavekar, Nandan S.
Abstract: Angiosarcomas are rare cancers accounting for less than 2% of all soft tissue sarcomas. We report the case of an unusual presentation of pleural epithelioid angiosarcoma in a patient with constrictive pericarditis and recurrent pleural effusion. A 62 year old smoker presented with acute chest pain. ECG showed diffuse elevation of ST segments in the precordial leads. After extensive evaluation, he was diagnosed with viral pericarditis and treated with colchicine. Two weeks later the patient presented to the emergency department with a large right pleural effusion. Evaluation of the pleural fluid obtained from a thoracentesis revealed an exudative effusion with negative microbial studies and no evidence of malignant cells. His pleural effusion re-accumulated rapidly, requiring repeated thoracenteses over several weeks. Medical thoracoscopy was performed and pleural biopsy revealed primary pleural epithelioid angiosarcoma. Staging PET scan revealed malignant enhancement of right pleura, pericardium, right iliac bone and right shoulder. He died suddenly within 6 weeks of diagnosis, prior to initiating palliative chemotherapy. Pleural angiosarcoma should be considered in the differential diagnosis of recurrent pleural effusions of unknown etiology. Negative cytology does not rule out the diagnosis; excisional biopsy is required. Reported risk factors include asbestos exposure, prior chest radiation, active smoking and history of complicated pleural tuberculosis. Pleural epithelioid angiosarcomas carry a very poor prognosis, with the majority of patients dying within months of diagnosis.